The Effect of Carbon on the Optimization of Physical Characteristics of Fe-Si-C Amorphous Ribbons - Ahmadov, V.I.; Isayeva, A.A.; Rafiyev, N.M. (Herald of Azerbaijan Engineering Academy, 2025)
This article extensively investigates the effect of carbon on the physical characteristics of Fe-Si-C amorphous ribbons. A detailed analysis was conducted on the structure, morphology, electrical, magnetic, and thermal properties of Fe-Si-C amorphous ribbon samples with varying carbon content. The study explores how changes in carbon concentration influence magnetic parameters such as saturation magnetization and coercive force, as well as the impact of carbon on the electrical resistance and thermal stability of the amorphous structure. The results indicate that the distribution of carbon within the structure and its interactions with other elements significantly affect the overall morphology and physical properties of the ribbons. Specifically, carbon content enhances structural stability and reduces the tendency of the amorphous phase to crystallize, thereby improving stability under high-temperature conditions. The potential application areas of the studied amorphous ribbons, including energy conversion and magnetic sensors, are also discussed. This work provides deeper insights into the role of carbon in adapting Fe-Si-C amorphous ribbons for various applications and serves as a foundation for future research.